Achieving digital health sustainability: Breaking Free and CGL. Issue 2 (5th June 2017) - Ward, Jonathan; Davies, Glyn; Dugdale, Stephanie; Elison, Sarah; Bijral, Prun
Abstract : Purpose: Multiple challenges remain in achieving sustainability of digital health innovations, with many failing to realise their potential due to barriers to research, development and implementation. Finding an approach that overcomes these challenges is important if society is to derive benefit from these new approaches to healthcare. Having been commissioned by local authorities, NHS Trusts, prisons, charities, and third sector providers across the UK, Breaking Free Group, who in 2010 launched Breaking Free Online (BFO), a computer-assisted therapy programme for substance misuse, have overcome many of these challenges. This has been possible through close collaborative working with partner organisations, to overcome barriers to implementation and sustainability. The paper aims to discuss these issues. Design/methodology/approach: This paper synthesises findings from a series of qualitative studies conducted by Breaking Free Group in collaboration with health and social care charity, Change, Grow, Live (CGL), which explore barriers and facilitators of implementation and sustainability of BFO at CGL. Data are analysed using thematic analyses with findings conceptualised using behavioural science theory. Findings: This partnership has resulted in UK wide implementation of BFO at CGL, enhanced focus on digital technologies in substance misuse recovery, and a growing body of published collaborative research. Originality/value: Valuable lessons have been learnt through the partnership between Breaking Free Group and CGL, which will be of interest to the wider digital health community. This paper outlines those lessons, in the hope that they will provide guidance to other digital health developers and their partners, to contribute to the continued evolution of a sustainable digital health sector.